Multi-Focal Diffractive Lens by Apodized Phase Photon Sieves - Ahmet Ünal (Gazi Üniversitesi Fen Bilimleri Dergisi)
As a result of the invention of photon sieves and the implementation of apodization to these sieves, significant design freedom has been achieved in diffractive optical elements (DOEs). Thanks to this freedom, secondary maxima in the intensity distribution can be reduced relative to the same photon sieves without apodization. In this study, unlike traditional methods, applying the apodization to phase types of photon sieves using metallic structures is discussed. Thus, not only intensity distributions are adjusted, but also electromagnetic interference (EMI) shielding is achieved. For this purpose, an Apodized Multi-focal Diffractive Lens (AMDL), which can be defined as a hybrid lens, was designed within the scope of this study, and its results were compared with its alternative, Multi-focal Diffractive Lens (MDL). During the design stage, simulations were carried out on two different bands. While the simulations in the optical band were performed using optical wave propagation, the simulations in the RF band were carried out using CST software, and the results were shared. As can be seen from the results, the secondary maxima in the intensity distribution was reduced due to the apodization, and EMI protection was also achieved. This study will contribute to the development of lenses designed for two different purposes called hybrid lenses in this research.